Investigation of the Cauchy problem for stochastic partial differential equations - Perun, H. M.; Yasinsky, V. K. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
It is shown that the solutions of stochastic linear parabolic equations with Poisson perturbations are stabilized in the mean square. The problem of determining the reserve of stability for a rod under random perturbations is studied.